Federalism the case of Switzerland - Linder, Wolf (2002)
Federalism remains one of the most important elements of modern statehood. It allows for highly decentralized governance close to the people, for public services and goods of high quality at low tax-level for the citizens, and for a civic culture trusting the capacities of small political units. Historically speaking, the Swiss federation can be considered as a case of "non-centralization." During the creation of the federation in 1848, the cantons kept their statehood, their constitutions and most of their political autonomy. Today, the central government is controlling only about 30 percent of the overall public budget; thus the Swiss federation has remained one of the most decentralized countries. In a historical perspective, federalism has allowed Swiss nation building as a bottom up process. As an element of political power sharing, federalism protected some minorities, the cultural heritage and diversity of the cantons, and helped to integrate the different segments of Swiss society. In a comparative perspective, Switzerland belongs to the good cases in which federalism has helped to deal peacefully or even to avoid multicultural conflict. Morever, the Swiss case illustrates the possibility of successful nation building despite cultural fragmentation. Both points are important today, as many young democracies of developing countries are facing similar conditions.
Keywords: Federalism -- Switzerland; Politics and government -- Switzerland